Comparison of the anthropometrics, kinematics and kinetics in young swimmers of different competitive levels - Barbosa, Tiago M. (2018)
The biomechanics plays a major role in the performance delivered by young swimmers. However, the literature addresses mostly the differences in the kinematics across young swimmers of different competetive levels, being scarce on the kinetics. The aim was to compare the anthrpmetics, kinematics and kinetics in young swimmers of different competetive levels.